Edukasi Tentang Hiperemesis Gravidarum di Wilayah Kerja Puskesmas Rejosari Pekanbaru - Rika Ruspita; Rifa Rahmi; Wira Ekdeni Aifa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Hyperemesis Gravidarum is nausea and vomiting during pregnancy. Although complaints of nausea and vomiting are considered normal for pregnant women and do not harm the fetus in the womb. However, if the frequency of nausea and vomiting is excessive, caution is still needed. Nausea followed by severe vomiting can be a sign of a problem with your pregnancy. For example in wine pregnancy, where the placenta develops into a group of abnormal cysts. Another possibility is hyperemesis gravidarum, which is a condition when pregnant women lose large amounts of body weight and body fluids. So that nausea and vomiting need to be avoided by being given drugs or other alternatives to reduce the complaint. So that education is needed about hyperemesis gravidarum to mothers who experience nausea and vomiting. The purpose of this activity is to provide education about hyperemesis gravidarum. The subjects of this community service activity are pregnant women in the Rejosari Health Center, Pekanbaru. Community service activities are supported by extension methods, question and answer, and discussion. The results showed that the participants were able to understand about emesis gravidarum, including understanding, causes, predisposing factors, and handling of emesis gravidarum.